(untitled) (Revista Brasileira de Estudos da Homocultura, 2024)
Discussions about politics and media, reality and fiction, going over topics such as support for the LGBT+ community and assumption of sexuality, have been recurrent among boys love (BL) fans both in Brazil and abroad. I will address part of the discourses on LGBT+ representation in BL series by the Brazilian fandom and offer an overview of how some of these debates have unfolded both in East and Southeast Asian countries and in Brazil, and what they may mean, seeking a better understanding of the nuances that surround them. For that, I have used as a basis ethnographic and digital fieldwork in the Brazilian BL fandom and literature that explores this dimension of the consumption experience of BL series in other East and Southeast Asian countries, such as China and the Philippines. Among the conclusions, I highlight that, despite the mistrust of the representational potential of BL series, they are presented by fans as a space of alternative representation and experimentation of other possible worlds.